Integration Of Sustainability Accounting in Management Control Systems And Its Impact on Company Performance - Mitha Christina Ginting; Farida Sagala; Lamria Sagala; Arthur Simanjuntak; Gracesiela Yosephine Simanjuntak (Jurnal Ilmiah Accusi, 2026)
This study examines the integration of sustainability accounting within Management Control Systems (MCS) and its impact on company performance among publicly listed companies in Indonesia. Method: Using a quantitative approach, data were collected from 112 non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Sustainability Accounting Integration (SAI) was measured using a composite index comprising environmental, social, and governance (ESG) disclosures, sustainability-linked performance indicators, and formal MCS–sustainability alignment. Company performance was measured using Return on Assets (ROA), Tobin's Q, and a balanced scorecard-based performance index. Structural Equation Modeling–Partial Least Squares (SEM-PLS) and panel data regression were employed for hypothesis testing. Findings: The results indicate that sustainability accounting integration significantly and positively affects both financial performance (ROA: β = 0.312, p < 0.001; Tobin's Q: β = 0.287, p < 0.001) and non-financial performance. MCS serves as a significant mediator between sustainability accounting practices and company performance, particularly through the planning and monitoring control subsystems. Companies in the extractive, manufacturing, and consumer goods sectors exhibited the strongest integration effects. Novelty: This study extends prior literature by empirically demonstrating the mediating role of MCS in translating sustainability accounting commitments into measurable performance outcomes, offering a novel integrated framework applicable to emerging market contexts